2023
DOI: 10.1002/ece3.9625
|View full text |Cite
|
Sign up to set email alerts
|

The Drosophila‐parasitizing wasp Leptopilina heterotoma: A comprehensive model system in ecology and evolution

Abstract: The parasitoid Leptopilina heterotoma has been used as a model system for more than 70 years, contributing greatly to diverse research areas in ecology and evolution. Here, we synthesized the large body of work on L. heterotoma with the aim to identify new research avenues that could be of interest also for researchers studying other parasitoids and insects. We start our review with a description of typical L. heterotoma characteristics, as well as that of the higher taxonomic groups to which this species belo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 383 publications
(731 reference statements)
0
6
0
Order By: Relevance
“…Increased expression levels of hpd may lead to a faster cuticle maturation of parasitoid wasp larvae, thus enhancing their ability to defend against the host immune responses and improve their survival. Given that parasitoid larvae obtain all the necessary nutrients from their hosts, they directly derive lipids from their hosts, consequently diminishing their own ability for lipid synthesis [51][52][53]. This adaptation was further evidenced by the two upregulated host fatty acid synthesis genes (FASN1 and ACC), supporting the perspective that parasitoids regulate the host's lipid metabolism for their own benefit.…”
Section: Discussionmentioning
confidence: 83%
“…Increased expression levels of hpd may lead to a faster cuticle maturation of parasitoid wasp larvae, thus enhancing their ability to defend against the host immune responses and improve their survival. Given that parasitoid larvae obtain all the necessary nutrients from their hosts, they directly derive lipids from their hosts, consequently diminishing their own ability for lipid synthesis [51][52][53]. This adaptation was further evidenced by the two upregulated host fatty acid synthesis genes (FASN1 and ACC), supporting the perspective that parasitoids regulate the host's lipid metabolism for their own benefit.…”
Section: Discussionmentioning
confidence: 83%
“…Invasive species lack this coevolutionary relationship, which raises questions about how they interact with parasitoids of established drosophilids (Kraaijeveld et al 1998). Leptopilina heterotoma is a generalist parasitoid wasp found in North America that parasitizes larvae of numerous drosophilid species due to its low selection threshold (Quicray et al 2023, de Bruijn et al 2022). Although L. heterotoma is a generalist, not all hosts are suitable for parasitoid development (Quicray et al 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Leptopilina heterotoma is a generalist parasitoid wasp found in North America that parasitizes larvae of numerous drosophilid species due to its low selection threshold (Quicray et al 2023, de Bruijn et al 2022). Although L. heterotoma is a generalist, not all hosts are suitable for parasitoid development (Quicray et al 2023). When examining Z. indianus' cellular immune response to parasitization, Kacsoh et al (2014) found that while L. heterotoma detects Z. indianus as potential hosts (e.g., ovipositing in larvae), the majority of Z. indianus successfully emerged as adults, suggesting that the immune system of Z. indianus is resistant to L. heterotoma.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, parasitoids may use chemical cues associated with the host they developed from to inform their future foraging behaviors ( Pomari-Fernandes et al 2015 , Bertin et al 2017 ). Finding and recognizing hosts in the field can be a complex challenge for female parasitoids ( Fellowes et al 2023 , Quicray et al 2023 ) and may be more difficult for parasitoids that utilize cues associated with hosts employed in artificial rearing systems ( Gandolfi et al 2003 ).…”
Section: Introductionmentioning
confidence: 99%